The concepts and methods of Western Chinese learning in the early period: A study based on Spanish missionary Francisco Varo’s Arte de la lengua Mandarina - 耿直, Zhi Geng (Círculo de Lingüística Aplicada a la Comunicación, 2018)
Spanish missionary Francisco Varo (1627-1678) is a pioneer in the history of Western and Chinese cross-cultural communication and Chinese Linguistics. His work Arte de la lengua Mandarina (Grammar of the Mandarin Language, written in 1682 and published in 1703) is not only one of the earliest Chinese grammar books officially published, but also a Chinese language teaching material especially designed for western missionaries. Its significance for the studies of the history of Chinese linguistics and social-culture has aroused concerns in the academic circle over last decade. However, its enlightening meanings as a Chinese second language textbook is undervalued. From the view of second language teaching, this paper discusses the language teaching concepts and methods of the early western Chinese learners reflected in the book and discloses its implications to the international Chinese language education at present.
Keywords: Spannish missionary; westerner; Chinese learning; Francisco Varo; Arte de la lengua Mandarina (Grammar of the Mandarin Language)